Social Participation and Mental Health among Older Adults (ongoing project) - Bobrowicz-Campos, E.; Silva, R.; Jøranson, N.; Zechner, M. (2025)
Despite longevity being a long-term goal, population ageing is discussed mainly with a focus on the challenges. The needs of support and care of older persons are often presented as burdens to family members and welfare states. Additionally, dementia and memory illnesses are significant threats to everybody, and loneliness in old age is becoming increasingly common as older persons are often left marginalised in society. To avoid marginalising oler people, social participation is vital. It can be informal, meaning that older persons have the opportunity and resources to socialize with other people, families, friends, peers, or meet occasional acquaintances in a nearby café or park. Social participation can also be formal, such as being active in politics, non-governmental organisations, churches, or societies. Both types of social participation have the potential to increase positive feelings in the person, such as belonging, meaning of life and happiness. Positive feelings again promote psychological wellbeing and mental health in general. This Special Issue focuses on interconnections between different types of social participation and their connections with mental health. With this Special Issue, we intend to - Pay special attention to positive aspects, possibilities and consequences, of social interaction and mental health in old age; - Provide new insights into factors that facilitate or hinder the social participation of older adults and broaden the knowledge about the associations between these factors and mental health; - Go beyond traditional perspectives on the role of community in supporting older persons and reflect on new solutions that, on the one hand, identify these persons as active agents and mobilize them to participate and, on the other hand, encourage the creation of living conditions and environments that support healthy and active living and ageing in place, involving families and communities; - Map promotional and interventional approaches that encourage social participation to enhance quality of life and well-being in advanced age and learn about their feasibility, appropriateness, meaningfulness and effectiveness from the perspective of providers, users or users’ relatives; - Propose to analyze the opportunities and challenges associated with ageing in the community, taking as a starting point the social, cultural and economic societal contexts ini which older persons live. We welcome primary and secondary research, empirical (qualitative, quantitative and mixed method) and theorical contributions, from different knowledge domains.